Exploration of open source in low-income countries: Review and future research directions - Silva, D.; Coutinho, C.; Costa, C. J. (2024 International Symposium on Sensing and Instrumentation in 5G and IoT Era (ISSI), 2024)
Free and open-source software (FOSS) is essential in the digital age, offering cost-effective and flexible solutions globally, especially in developing countries. This study employs bibliometric and systematic review methods to analyze 897 articles published between 2001 and 2023, focusing on key themes like health, costs, and information systems. The analysis identified emerging areas such as low-cost technology, applied engineering, the Internet of Things (IoT), educational informatics, and digital health as promising fields for future research. The findings underscore the potential of FOSS to enhance information systems, reduce costs, and support digital development policies. These insights can inform strategies to maximize FOSS’s impact, driving digitalization and innovation in emerging economies and contributing to global technological progress.